Hypomagnesemia as a Predictor of Early Liver Dysfunction in Critically Ill Patients with Sepsis - Ayşegül İlban; Ömür İlban (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: Liver dysfunction is an early finding caused by the inflammation and hypoperfusion developed in sepsis. Magnesium deficiency may contribute to an excessive response to immune stress and inflammatory tissue damage in sepsis. This study aimed to evaluate the relationship between serum magnesium levels and early liver dysfunction (ELD) in patients with sepsis. Material and Methods: 142 patients who developed sepsis were divided into two groups according to their liver function, as sequential organ failure assessment (SOFA) hepatic subscore <2 (Non-ELD, n=72) and SOFA hepatic subscore ≥2 (ELD, n=70). The disease severity, including the acute physiology and chronic health evaluation (APACHE) II score and the SOFA score, biochemical determination, and microbiological cultures were evaluated. Results: ELD patients presented APACHE II and total SOFA scores higher than Non-ELD patients, while PaO2/FiO2 ratios were significantly lower (both p<0.001). Hypomagnesemia and hypoalbuminemia were independently associated with ELD (OR: 6.55, 95% CI: 2.62-16.36, and OR: 4.62, 95% CI: 1.35-15.84, respectively). To predict ELD, the area under the curve was 0.81 (95% CI: 0.74-0.89, p<0.001) and 0.70 (95% CI, 0.61-0.79; p<0.001) for serum magnesium and albumin, respectively. The mortality rate in all septic patients was 35.0% for hypomagnesemia and 25.6% for normomagnesemia (p=0.065). The mortality rate in ELD patients was 34.1% for hypomagnesemia and 30.7% for normomagnesemia (p=0.415). Conclusion: The reduction of magnesium levels was associated with increased rates of ELD in critically ill patients with sepsis. Admission hypomagnesemia did not adversely affect mortality neither in all sepsis patients nor in those who developed ELD.